2009
DOI: 10.1186/1750-4732-3-9
|View full text |Cite
|
Sign up to set email alerts
|

The immediate effect of individual manipulation techniques on pulmonary function measures in persons with chronic obstructive pulmonary disease

Abstract: Background: The use of manipulation has long been advocated in the treatment of chronic obstructive pulmonary disease (COPD), but few randomized controlled clinical trials have measured the effect of manipulation on pulmonary function. In addition, the effects of individual manipulative techniques on the pulmonary system are poorly understood. Therefore, the purpose of this study was to determine the immediate effects of four osteopathic techniques on pulmonary function measures in persons with COPD relative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 7 publications
1
64
1
4
Order By: Relevance
“…This is highlighted by results from two studies that reported an immediate worsening of air trapping in people with COPD following the administration of soft tissue techniques that appeared to shift this balance in the wrong direction. 31,32 It is worth noting that, notwithstanding the screening process for contraindications conducted before MT being administered, no moderate or major AEs were reported in any participant who received MT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is highlighted by results from two studies that reported an immediate worsening of air trapping in people with COPD following the administration of soft tissue techniques that appeared to shift this balance in the wrong direction. 31,32 It is worth noting that, notwithstanding the screening process for contraindications conducted before MT being administered, no moderate or major AEs were reported in any participant who received MT.…”
Section: Discussionmentioning
confidence: 99%
“…30 There is some evidence to show that direct application of MT to the chest wall benefits patients with chronic respiratory disease. Soft tissue-focused techniques have been used with mixed success in the management of COPD 31,32 and pneumonia in the elderly, [33][34][35] 39,40 Measuring the effect of combining these two types of MT with exercise raises the question: are both types of MT required in order to achieve the improvements in lung function and exercise capacity? Reports that some soft-tissue techniques produce a worsening in pulmonary function immediately postintervention when applied on their own 31,32 suggest that this form of MT may need to be administered in conjunction with joint-focused MT in order to produce improvements in lung function in people with COPD.…”
Section: Introductionmentioning
confidence: 99%
“…4 The aim of most of these techniques is to increase movement in the rib cage and the spine in order to improve lung function and circulation. 5,6 However, two different systematic reviews 4,7 have examined the role of manual therapy in pulmonary pathologies, concluding that there is a lack of high quality research in this area and showing no evidence for the application in patients with chronic obstructive pulmonary disease or asthma. Additionally, the use of manual therapy in the thorax can be used as a therapeutic approach to dysfunctional breathing, a respiratory disorder involving an overt hyperventilation and hypocapnia and/or more subtle and subjective features.…”
Section: Introductionmentioning
confidence: 99%
“…The approach to the patient varies widely, both in terms of techniques and time management: thoracic spinal mobilization, lymphatic drainage or pump, diaphragmatic release trigger points, massage, articulation techniques for ribs, myofascial release to the thoracic outlet, suboccipital decompression, and muscular stretching 16,37,38. The results of the various respiratory parameters are always positive, but we have not enough information to draw definitive conclusions.…”
Section: Manual Therapy and Diaphragmmentioning
confidence: 99%